PERBEDAAN DARAH SEGERA DIPERIKSA, DILAKUKAN PENYIMPANAN PADA SUHU 20ºC-25ºC DAN 4ºC-8ºC SELAMA 6 JAM TERHADAP JUMLAH ERITROSIT - Ferdi Afriansyah; Bastian Bastian; Indah Sari; Denny Juraijin (Journal of Indonesian Medical Laboratory and Science, 2021)
Errors that often occur in laboratory examinations are in the pre-analytic stage with an error percentage of 50%-75%. Examination of blood samples to maintain conditions so that they are not damaged, the samples are usually stored at a temperature 4-8oC for several hours to 4-5 days and blood specimens stored temperature of 20-24oC for a maximum examination 24 hours. However, the examination of the number of erythrocytes should be carried out immediately after collection without storage because the delay in examination time can affect the number of erythrocytes, the longer the delay, the number of erythrocytes decreases because the cells undergo hemolysis, biochemical, biomechanical and immunological reactions. This researcher aims to determine the difference in blood immediately examined, blood stored temperature of 20oC-25oC and 4oC-8oC for 6 hours on the number of erythrocytes. The research design used a true experiment with a pre-test design and a post-test control group design with a hypothesis test using the Two-way ANOVA test. This research was conducted 30 respondents of DIV Medical Laboratory Technology students. The results of the study the number of erythrocytes in the blood immediately with an average value of 4.57 million/µI, at a temperature of 20oC-25oC has an average value of 4.65 million/µL, temperature of 4oC-8oC has an average value of 4.50 million/µL and Friedman test obtained p value = 0.172. Conclusion of the study showed that there was no difference in blood immediately examined, the blood was stored at a temperature of 20oC-25oC and 4oC-8oC for 6 hours on the number of erythrocytes.